2016
DOI: 10.1017/s1041610216000958
|View full text |Cite
|
Sign up to set email alerts
|

The association of timing of retirement with cognitive performance in old age: the role of leisure activities after retirement

Abstract: Present data further corroborate the view that leisure activities even in old age may lead to further enrichment effects and thereby may be related to better cognitive functioning. The role of engaging in activities in the context of major life events such as retirement is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
51
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(56 citation statements)
references
References 31 publications
5
51
0
Order By: Relevance
“…Our observations corroborate the key role of leisure activity engagement as major contributor to cognitive reserve for modifying the pathways of cognitive aging [5][6][7][8][16][17][18] and thereby its public importance [19][20][21]. In this regard, the present study reveals cognitive reserve as crucial factor moderating the predictive role of memory complaints for subsequent cognitive development.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Our observations corroborate the key role of leisure activity engagement as major contributor to cognitive reserve for modifying the pathways of cognitive aging [5][6][7][8][16][17][18] and thereby its public importance [19][20][21]. In this regard, the present study reveals cognitive reserve as crucial factor moderating the predictive role of memory complaints for subsequent cognitive development.…”
Section: Discussionsupporting
confidence: 88%
“…In both waves, we administered the TMT parts A and B (TMT A and TMT B, respectively [15]). In W1, participants reported memory complaints as well as current leisure activity engagement at that time (see [8] for further methodological details).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Disentangling the individual contributions to cognitive reserve accumulation across the lifespan, we found that (in contrast to education and cognitive demand of jobs) leisure activity engagement played the key role in this context. Thereby, our observations dovetail with findings that greater leisure activity engagement contributes to cognitive reserve and is associated with better performance and reduced decline in executive functioning [5,[14][15][16] and are therefore of public importance [17,18]. In this regard, the present study further elucidates leisure activity engagement as crucial cognitive-reserve proxy contributing to the build-up of a buffer prior to stroke that will be later instrumental for coping with stroke-related brain damage.…”
Section: Discussionsupporting
confidence: 84%